Sistem Mikrokontroler Untuk Menentukan Kualitas Air Yang Dapat di Gunakan Oleh Konsumen dengan Menggunakan Arduino - Fahri Rahmadani; Suhada Suhada; Bahrudi Efendi Damanik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
There are now many businesses that provide refilled drinking water in every big city, because besides that, the price that is not too expensive can save time because there is no need for difficulties in obtaining clean water. The owner of the drinking water business still does not know whether the water produced is fit for consumption. Therefore, a tool will be made to measure air quality based on the selected parameter, namely the pH value of the water by using a pH meter sensor based on Arduino Uno and displayed through an LCD screen so that you can see directly the results of the refilled water test.